Perancangan Website sebagai Media Informasi dan Peningkatan Citra Pada SMK Dewi Sartika Tangerang - Wendy Andriyan; Sarwan Septiawan Septiawan; Annisa Aulya (Jurnal Teknologi Terpadu, 2020)
Many schools are currently competing to make information and promotional media as attractive as possible, which attract attention in obtaining prospective students and new students. Most of the media used by schools still have limitations in their delivery. They are deemed inefficient because people have to come to the school directly to get information about schools. This is experienced by SMK Dewi Sartika Tangerang, where the information and promotion media used are still printed media such as brochures and banners. As a private school, of course, this is a problem in competition with other schools to get new students, and the image of the school is less well known by the public. Therefore, it is necessary to have additional media with a broader scope of information access and promotion so that many people know and are interested in SMK Dewi Sartika Tangerang. One of the efficient media that can be used to support information and promotion is a website in which there is information in the form of text, images, videos, sounds, and various other features to understand the information conveyed quickly and clearly. This study uses field research methods to collect data through observation, interviews, and documentation. There is also problem analysis, needs analysis, and testing methods using black-box testing to determine whether the website is as expected. This study produces a website design that can be implemented by SMK Dewi Sartika Tangerang so that the community's needs for information sought about schools can be fulfilled. With this research, the authors hope to increase the acquisition of target students who are higher and improve the school's image in the eyes of the community.